Sema3a as a Novel Therapeutic Option for High Glucose-Suppressed Osteogenic Differentiation in Diabetic Osteopathy - Zhang, Lixia; Zheng, Lili; Li, Chong; Wang, Zhifang; Li, Shan; Xu, Lijun (Frontiers in Endocrinology, 2019)
Objective: Diabetic osteopathy is a common comorbidity of diabetes mellitus, with skeletal fragility, osteoporosis and bone pain. The aim of our study was to highlight the role of sema3a on osteoblast differentiation of MC3T3-e1 in high-glucose condition and explore its therapeutic effect of diabetic osteopathy in vitro and vivo. Methods: In our study, the expression of osteogenesis-related makers, such as ALP, OCN, OPG, β-catenin and Runx2, were analyzed in MC3T3 osteoblastic cells to explore the effect of sema3a on osteoblast differentiation in high-glucose condition, and as was the staining of ALP and Alizarin Red S. In a diabetic animal model, the expression of serum bone metabolic markers, such as ALP, P1NP, OCN, and β-CTX, were analyzed and micro-CT was used to detect bone architecture, including Tb.N, Tb.Th, Tb.Sp, Tb.Pf, BS/BV, and BV/TV after the treatment of sema3a. Results: High glucose significantly inhibited osteogenic differentiation by decreasing the expression of osteogenesis-related makers, sema3a and its receptor of Nrp-1 in a dose-dependent manner in MC3T3. In high-glucose condition, exogenous sema3a (RPL917Mu01) increased the expression of ALP, OCN, OPG, Runx2, β-catenin, and the positive proportion of ALP and Alizarin Red S staining. In addition, in diabetic animal model, exogenous sema3a could increase bone mass and bone mineral density, and downregulate the expression of ALP, P1NP, OCN, and β-CTX. Conclusion: High glucose suppresses osteogenic differentiation in MC3T3 and sema3a may take part in this process. The application of exogenous sema3a alleviates high glucose-induced inhibition of osteoblast differentiation in diabetic osteopathy.